“SELLING” The Beauty Of Priangan In The Dutch Colonial Era - Hermawan, Iwan (Kodepena Indonesia, 2023)
During the Dutch colonial era, Priangan was one of the most famous tourist destinations in the archipelago. They came from all over the world to enjoy the beauty and coolness of Priangan's nature. The problem discussed in this paper is how tourism development efforts in the Priangan region. In order to achieve the purpose of the writing, a descriptive method is used. Data collection is done through literature study. The results showed that easy access to tourist attractions and the provision of adequate accommodation and promotion are the main capital in the development of tourism in Priangan. The success was achieved due to the support and participation of the community in the development and promotion of tourist attractions in the Priangan region.